2004
DOI: 10.1111/j.1440-1754.2004.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in identifying neonatal percutaneous central venous line position

Abstract: Interobserver and intraobserver reliability was poor when using radiographs to assess long line tips. The major determinant of line repositioning was the perceived location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In retrospect, this estimate was overly optimistic, as there was only 75% agreement in the 12 infants where both operators could identify the line position with colour Doppler. This degree of agreement is similar to that seen with the radiographic assessment, which – despite being regarded as the gold standard for localising longline position – ranges between 40 and 88%, with considerable intra‐observer variability 12 . Although digital radiography has been reported to improve the visibility of longline tip position compared with the hard copy films, 13 it does not necessarily improve the agreement between observers despite the ability to manipulate image quality 9 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In retrospect, this estimate was overly optimistic, as there was only 75% agreement in the 12 infants where both operators could identify the line position with colour Doppler. This degree of agreement is similar to that seen with the radiographic assessment, which – despite being regarded as the gold standard for localising longline position – ranges between 40 and 88%, with considerable intra‐observer variability 12 . Although digital radiography has been reported to improve the visibility of longline tip position compared with the hard copy films, 13 it does not necessarily improve the agreement between observers despite the ability to manipulate image quality 9 .…”
Section: Discussionsupporting
confidence: 73%
“…This degree of agreement is similar to that seen with the radiographic assessment, which -despite being regarded as the gold standard for localising longline positionranges between 40 and 88%, with considerable intra-observer variability. 12 Although digital radiography has been reported to improve the visibility of longline tip position compared with the hard copy films, 13 it does not necessarily improve the agreement between observers despite the ability to manipulate image quality. 9 The level of agreement of longline position between radiology observers in this study (68%) is similar to our previous studies using contrast radiography 14 and digital radiography.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size used in this study was consistent with those used in similar studies reported in the literature. 12,16 All CXRs were acquired to a standard technique 17 and acceptable image quality was verified by two of the study authors.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely speculated that assessment of catheter tip position on CXR is inaccurate and subject to interobserver variability. [11][12][13][14][15] For CXR to be a valid tool it would require that a radiologist is able to reliably identify the CAJ position. To our knowledge, the accuracy of this task, in this specifically trained group, has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods are used to assess longline tip position. The most common, plain radiography is plagued with concerns about poor intra- and inter-observer reliability[ 2 ]. Other modalities, e.g ., echocardiography[ 3 ] and CT[ 4 ] might be more reliable but are not readily available in most units.…”
Section: Introductionmentioning
confidence: 99%